Anticancer and Antimalarial Assays of Xanthone-Fatty Acid Hybrids: Integrative In Vitro and In Silico Evaluation - Kurniawan, Yehezkiel Steven; Harizal, Harizal; Yudha, Ervan; Gurning, Kasta; Pranowo, Harno Dwi; Sholikhah, Eti Nurwening; Jumina, Jumina (Universitas Gadjah Mada, 2025)
Cancer and malaria are two fatal diseases found in Indonesia over the past several years. Therefore, researchers are trying their best to find new anticancer and antimalarial agents. In the present work, we evaluated five xanthone-fatty acid hybrids, i.e., xanthyl laurate (XL), xanthyl myristate (XM), xanthyl palmitate (XP), xanthyl stearate (XS), and xanthyl oleate (XO), as novel anticancer and antimalarial agents. The cytotoxicity assay towards NIH3T3 reveals that xanthone-fatty acid hybrids showed a selectivity index up to 282.08, demonstrating their non-toxic profile. The MTT assay found that XO yielded stronger breast anticancer activity than doxorubicin as the positive control. All xanthone-fatty acid hybrids exhibited moderate antimalarial activity with IC50 values of 24.24–87.57 µM, lower than that of chloroquine diphosphate as the positive control (4.26 µM). As the best anticancer agent for breast cancer, the mode of action of XO was further studied by computational studies. The molecular docking results showed the binding energy against the HER2 protein was −45.73 kJ/mol through a hydrogen bond with Lys753. This hydrogen bond remained stable until the end of the molecular dynamics simulations for 100 ns. These findings highlight the potential application of XO as a new drug candidate for breast cancer treatment.